Agnostiska tankar om döende och död (Sociologisk Forskning, 1996)
Some agnostic thoughts about dying and deathI take my point of departure in an agnostic and liberal view. People should be offered such forms of dying and death that fit their cosmology and views of the good life and death. Not believing in a life after corporal death means emphasising everyday life and social networks. The paper has four themes: 1) The tendency to conceal and deny death as an existential condition of life needs to be analysed and questioned. 2) Dying and death are sequestrated in modem society and should be brought together with everyday life. 3) The medical control and steering of the dying process is based on some evaluative presumption that needs to be elucidated and discussed. 4) Human sciences should give more attention to the social consequences of death and the shaping of such institutional rites of passage from living to dead that consoles, reliefs, confirms, reconciles, reintegrates and supports the immediately involved.